Risk factors for delayed wound healing after anal fistula surgery: Protocol of a meta-analytic study - Zubing Mei; Peixin Du; Ye Han; Yin Qu; Huili Tang; Yan Li; Huiyan Gao; Qingming Wang; De Zheng (PLoS ONE, 2025)
Introduction Delayed wound healing (DWH) following anal fistula surgery is a common complication that prolongs recovery, increases patient morbidity, and imposes significant healthcare costs. Potential risk factors such as diabetes, smoking, fistula complexity, and surgical techniques have been suggested in individual studies, yet no comprehensive synthesis exists to guide clinical practice. This study aims to identify and evaluate risk factors associated with DWH after anal fistula surgery by combining existing evidence and grading the evidence. Methods and analysis This study will follow the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) guidelines. We will search PubMed, Embase, Cochrane Library, Web of Science, and grey literature databases from inception to March 2025, with no language restrictions. Observational studies (cohort and case-control) reporting risk factors for DWH, defined as incomplete healing beyond 6–12 weeks post-surgery, will be included. Two independent reviewers will screen titles/abstracts, perform full-text reviews, extract data regarding study design, sample size, risk factors and outcomes, and assess risk of bias using the Newcastle-Ottawa Scale (NOS). Primary outcomes will include odds ratios (OR) or relative risks (RR) for factors such as comorbidities, lifestyle factors, and operative approaches. A random-effects meta-analysis will pool effect estimates if heterogeneity (I² < 50%) permits; otherwise, a narrative synthesis will be conducted. Subgroup analyses will explore differences by study design and patient characteristics, with publication bias assessed using funnel plots and Egger’s test. The certainty of evidence will be evaluated with the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Discussion This study’s strengths include its comprehensive search strategy and rigorous methodology, providing a robust synthesis of risk factors. Clinically, identifying modifiable risk factors could enhance preoperative optimization and postoperative care, reducing delayed healing rates. Future studies should standardize definitions of delayed healing and explore under-investigated factors like wound care techniques or microbiome influences to refine risk prediction models. Registration PROSPERO CRD420251013602